Canthaxanthin, a Red-Hot Carotenoid: Applications, Synthesis, and Biosynthetic Evolution - Bárbara A. Rebelo; Sara Farrona; M. Rita Ventura; Rita Abranches (Plants, 2020)
Carotenoids are a class of pigments with a biological role in light capture and antioxidant activities. High value ketocarotenoids, such as astaxanthin and canthaxanthin, are highly appealing for applications in human nutraceutical, cosmetic, and animal feed industries due to their color- and health-related properties. In this review, recent advances in metabolic engineering and synthetic biology towards the production of ketocarotenoids, in particular the red-orange canthaxanthin, are highlighted. Also reviewed and discussed are the properties of canthaxanthin, its natural producers, and various strategies for its chemical synthesis. We review the de novo synthesis of canthaxanthin and the functional β-carotene ketolase enzyme across organisms, supported by a protein-sequence-based phylogenetic analysis. Various possible modifications of the carotenoid biosynthesis pathway and the present sustainable cost-effective alternative platforms for ketocarotenoids biosynthesis are also discussed.